Physical and Chemical Characteristics of Sulawesi Cocoa Beans 2 (Theobroma cacao L) Fermented and Unfermented Result - Khaerunnisa, Khaerunnisa; Rosniati, Rosniati; Kalsum, Kalsum (Politeknik AKA Bogor, 2023)
This study aims to determine the physical and chemical characteristics of fermented and unfermented BR 25 clone dry cocoa beans. The treatment in this study was the fermented treatment (Treatment A) and the unfermented treatment (Treatment B). The fermented and unfermented treatments were processed from wet cocoa beans with 10 kilograms of beans for each treatment. The fermentation treatment uses a box of Styrofoam, while the unfermented treatment is directly dried in the sun after removing the mucus (pulp). The parameters for fermented and unfermented dry cocoa beans were water, pH, fat content, protein, polyphenols, antioxidant activity (IC50), and ALT. The results showed that fermented cocoa beans had a moisture content of 5.77%, pH of 6.41; fat content of 55.63%; protein of 14.36%; polyphenol content of 4.62%; antioxidant activity (IC50) of 21.96%; and ALT value of 1.0 x 102 colonies/gram. Unfermented cocoa beans have a moisture content of 6.52%, pH of 5.20; fat content of 59.63%; protein of 17.83%; polyphenol content of 2.06%; antioxidant activity (IC50) of 62.23%; and ALT value of 1.1 x 102 colonies/gram.Keywords: cacao beans; fermented; unfermented; characteristics